Narrative analysis of English language learning in intra-national migration in Korea: A case study on the development of academic literacy - Cho, Eunhae (System (Linköping), 2025)
This study uses narrative analysis to investigate the ontogenesis of one language learner's understanding of his own experiences. The subject of the study, a Korean college student, demonstrates a development in his understanding of language. Initially, he perceived language as a numerical score, but he gradually came to value it as a tool for conveying meaning, then ultimately reverted to a score-centered perspective. Employing reflective language learning journals and interviews over 16 weeks, this study examines the role of self-reflection in his evolving understanding of language and its learning. Using Vygotsky's frameworks of lived experience, which take cognition and emotion in dialectical unity to push development forward, this study reveals the impact of emotional responses, often triggered by regional disparities in educational resources, on the student's language learning and on his strategies for coping and mastering study skills. As the student navigates language learning while shuttling between two geographic realities, these emotional responses influence both his learning and his educational and occupational choices. By illuminating the intricate socially constructed emotional aspects intertwined with language learning, this research underscores the crucial role emotions play in language acquisition and overall personal growth.